PATTERNS OF DIGITAL INTERACTION THROUGH TIKTOK REPOSTING AND ITS RELATIONSHIP WITH THE EMOTIONAL STATE OF GENERATION Z - Muhammad Ijlal Sasakki Junaidi; Rabiatul Adawiyah (Universitas Negeri Surabaya, 2026)
The development of social media in the digital era has transformed patterns of social interaction, especially among Generation Z who have grown up with digital technology. TikTok, as a short-video-based platform, functions not only as an entertainment medium but also as a space for emotional expression and symbolic communication. One emerging form of interaction is reposting activity, which refers to resharing content perceived as relevant to users’ personal emotional conditions. This study aims to analyze digital interaction patterns through TikTok reposting and their relationship with Generation Z’s emotional conditions. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation involving five Generation Z informants who are active TikTok users. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by source triangulation to ensure data validity. The findings reveal that reposting is not merely a content-sharing activity but carries deeper psychological meaning. It functions as indirect self-expression, emotional regulation, and a form of social validation seeking within digital spaces. Reposted content reflects users’ emotional states such as sadness, anxiety, psychological pressure, as well as positive emotions. This activity generates psychological effects including emotional relief, social connectedness, and emotional fluctuations influenced by responses received from other users in social media environments.